Five-Year Outcome of the Venovo Venous Stent for the Treatment of Iliac Vein Compression: Results from a Single Center - Ayyoub, Abdullah; Shammas, Nicolas W.; Shammas, Gail A.; Jones-Mller, Sue (International Journal of Angiology, 2026)
The Venovo self-expanding venous stent (Bard/BD, New Jersey, United States) is approved for the treatment of symptomatic iliofemoral venous obstruction and demonstrated excellent 3-year outcomes in the pivotal VERNACULAR trial. Long-term (>3-year) data remain limited. This retrospective, single-center study evaluated 50 consecutive patients who completed 5-year follow-up after receiving the Venovo stent for symptomatic iliac vein compression. Data were extracted from medical records following approval by a central ethics committee. Of the 50 patients, 6 died and 1 was lost to follow-up. The primary endpoint was major adverse events at 5 years, including target lesion revascularization (TLR), target vessel revascularization (TVR), and mortality. Secondary analyses assessed changes in CEAP class, edema, and active ulceration compared with baseline. No TLR or TVR occurred during the 5-year follow-up. Six deaths were observed, none procedural or device-related. Overall survival was 87.8%. Duplex ultrasound demonstrated 100% patency. CEAP class significantly improved from baseline to 5 years (p = 0.0011), driven primarily by reduced edema and ulcer resolution. The Venovo venous stent demonstrated excellent long-term safety with 100% patency and no TLR at 5 years. Clinical improvement, including reduced edema and sustained ulcer healing, persisted throughout follow-up.
Keywords: Venovo stent; long-term outcome; target lesion revascularization; mortality; patency; CEAP class; edema